2012
DOI: 10.1177/0731684411433061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber volume fraction on the energy absorption capacity of composite materials

Abstract: In this investigation, the effect of fiber volume fraction on the energy absorption capacity of fiber-reinforced composite materials was studied using dynamic mechanical analysis measurements. Laminates were fabricated with and without vacuum bag using plain weave E-glass fabric and three types of polymer matrix: epoxy, polyester, and vinyl ester. The higher energy absorption displayed by samples processed under vacuum was related to the shorter distance between adjacent fibers which produces stresses of highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…8 Tensile stiffness may continue to increase with fiber volume fraction; the laminate's compressive strength will reach a peak and then it begins to decrease due to the lack of sufficient resin to arrest the fiber micro-buckling. 9 Test laminates of the subject study were characterized for fiber volume (V f ) and void fraction (V v ) as per ASTM D 3171. Results presented in Table 1 reveal that all the laminates have comparable fiber volume and void fraction.…”
Section: Resultsmentioning
confidence: 99%
“…8 Tensile stiffness may continue to increase with fiber volume fraction; the laminate's compressive strength will reach a peak and then it begins to decrease due to the lack of sufficient resin to arrest the fiber micro-buckling. 9 Test laminates of the subject study were characterized for fiber volume (V f ) and void fraction (V v ) as per ASTM D 3171. Results presented in Table 1 reveal that all the laminates have comparable fiber volume and void fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Haddad and Feng [42] further confirmed this tendency. Furthermore, the volume fraction of matrix for damping has been investigated and the results revealed that the damping ratio of three-layer-connected biaxial weft-knitted fabric reinforced composites increased with the increasing of matrix volume fraction [43]. The reason can be attributed to the higher stresses in the matrix due to closer spacing which resulted in higher energy dissipation capacity during the dynamic loading.…”
Section: Polymer Matrixmentioning
confidence: 99%
“…This could include deciding on the types of fiber and matrix to be used for each lamina, the volumetric ratio of the fiber, lamina thickness, orientation of the fiber in the lamina, the periodicity or randomness of the fiber in the microscale structure of the advanced composites, sequence of the laminas in the laminate and the resin used. [17][18][19] The final decision is an output of a complicated interactive process the boundary of which is the anticipated characteristics of the bridge structural systems and their performance under extreme loading conditions. Although following general material and sectional design regulations adopted from experience with traditional cable-stayed bridge systems is supposed to simplify and accelerate the analysis-design procedure, it does not guarantee that the structural system will pass all the limit states and the aerodynamic stability requirements.…”
Section: Micro/macro Level Design and Evaluation Of Advanced Composite Materialsmentioning
confidence: 99%